Sectarian Strife in Iraq, To where? And for Whom?: Causes, Implications, and Remedies - Hashim, Jabbar Mohammed (International Journal of Psychosocial Rehabilitation, 2019)
There is no doubt that sectarianism has abhorrent dimensions and negative roles that cast its shadows on the one people and the one nation, thus creating veils and differences between brotherhood and spreading poisons between the sides of the ideas and visions that it puts into place, and scattering the homes with blemishes through the creation of discrimination and the attempt to tear the sacred bond among people in general and adherents of the same faith in particular. That is why vigilance, caution, and deliberation in accusing the other and trying to understand them with an understanding are in line with the spirit of brotherhood and tolerance which make us all in one trench in order to expel and kill the yellow winds of sectarianism and racism and be at the level of the ambition of true humanity. This research came as a modest contribution to solving this crisis.